The minimum wage and firm networks: Evidence from South Africa - Brandon Joel Tan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
There is a large literature on the minimum wage focused on directly exposed firms and geographies. This paper provides new evidence that the minimum wage has significant spillover effects on firms exposed to the minimum wage indirectly via firm supply chains. Using administrative firm-level tax data from South Africa, we study the impact of the 50 per cent agricultural minimum wage hike in 2013 on the outcomes of firms downstream from the agriculture sector with an event study design. The minimum wage increased labour costs and prices in the agriculture sector. We find that industries with greater upstream exposure to the agriculture sector experienced greater decreases in assets, sales, and employment for medium to large firms following the minimum wage increase.
Keywords: J23; J31; J46; 330; minimum wage; supply chains